Effect of dietary inclusion of turmeric (Curcuma longa) on the intestinal parasite and egg quality characteristics of Quails (Agriculture, Food, and Natural Resources Journal, 2024)
The problem of antibiotic resistance in birds necessitates the search for alternatives. This study evaluated the effect of dietary inclusion of turmeric (Curcuma longa) on the intestinal parasite infestation and egg-laying performance of Japanese quails (Coturnix japonica). Forty-five points of lay quails were randomly assigned to three treatments: T1 received 3g of turmeric per 1 liter of water, T2 received 1 tea spoon (4.2g) of dewormer (Bactro-expeller) per 3 liters of water, and T3 served as the control without any test ingredient. The experiment lasted for six weeks, with three replicates of five quails each. Egg quality parameters such as albumen height, egg weight, yolk index, and yolk width were significantly affected by the treatments (P
Keywords: Dewormer; Intestinal parasite; Laying performances; Turmeric; Quails